Determinants of International Trade: Nepalese Perspectives - Aryal, Bibhu Prasad (New Perspective: Journal of Business and Economics, 2024)
This article aims to identify and analyze the economic determinants that directly influence Nepal's international trade activities. The analysis is divided into import and export models, utilizing secondary sources of annual data from July 1975 to July 2023. The study employs regression analysis to identify the relationships between the dependent and independent variables affecting trade performance. The regression model for imports (Model A) indicates that real GDP and the consumer price index (CPI) of India have significant positive effects on imports, with coefficients of 1.59 and 1.47, respectively, both statistically significant at the 1% level. Conversely, remittances show a strong negative effect on imports, with a coefficient of -0.13. For exports (Model B), the analysis reveals relationships between exports and three independent variables: the CPI in India, exchange rate, and real GDP. The CPI in India has a coefficient of -6.496, highly significant (p = 0.0000), indicating that a 1% increase in the CPI leads to approximately a 6.50% decrease in exports, highlighting a strong negative impact of rising prices in India on exports to Nepal. By addressing the identified economic determinants, policymakers can develop strategies to improve Nepal's international trade dynamics and overall economic resilience.